Shuudanshugi: Pembingkaian oleh Media Jepang dalam Pemberitaan Kondisi 10 Tahun Pasca Bencana Nuklir Fukushima Daiichi - Umar, Muhammad; Umoro, Anisa Ledy (East Asian Review, 2023)
Happened in 2011, Japanese people will never forget the Fukushima Daiichi Nuclear Disaster as one of the saddest memories. More than ten years passed, and now Fukushima is starting to “move.” As it aims to understand the pattern of how the media frames this news topic, this research explores how Japanese media frames the topic of how Fukushima is “moving” after ten years have passed since the disaster. To achieve its aim, this research employs thematic analysis of the news data that were gathered from YouTube. Through the analysis, how the Japanese media framed the news was thick with elements of collectivism, as it is seen that the media frames the city-society as a unity and has a strong correlation even to the socio-cultural level. Elaborated with Nakane’s (1989) frame and attribute, it can be seen that the media framed the city as a spatial communal frame that binds society as a single commune entity. This finding shows the media frames the city and society as one “group.” In conclusion, the framing carried out by the Japanese media was nuanced with the concept of shuudanshugi or “group-oriented.”